2010
DOI: 10.1542/peds.2009-1666
|View full text |Cite
|
Sign up to set email alerts
|

A “Novel” Intervention: A Pilot Study of Children's Literature and Healthy Lifestyles

Abstract: Age-appropriate fiction, particularly if it addresses health-oriented behaviors, shows potential for augmenting weight loss in girls who participate in a weight-management program. Future research is needed to determine if the novel is effective for healthy lifestyle promotion among all overweight and obese adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 12 publications
0
11
0
2
Order By: Relevance
“…Reading a storybook or listening to stories is helpful for children as it promotes pupils' emotional expression and psychological wellbeing; it can be used to stimulate changes in young people lifestyles, encouraging them in practicing physical activity and reducing the consumption of sweets and soft-drinks, ultimately resulting in a measurable reduction of body mass index in specific cohorts. 122 Bibliotherapy facilitates behaviour´s externalization, promotes empathy and prosocial behaviours, and helps solving problems such as bullying and teasing, which represent common situations in every school. Several studies have demonstrated the effectiveness of treating bullying through bibliotherapy, that can become an innovative approach to promote a respectful school environment.…”
Section: Discussionmentioning
confidence: 99%
“…Reading a storybook or listening to stories is helpful for children as it promotes pupils' emotional expression and psychological wellbeing; it can be used to stimulate changes in young people lifestyles, encouraging them in practicing physical activity and reducing the consumption of sweets and soft-drinks, ultimately resulting in a measurable reduction of body mass index in specific cohorts. 122 Bibliotherapy facilitates behaviour´s externalization, promotes empathy and prosocial behaviours, and helps solving problems such as bullying and teasing, which represent common situations in every school. Several studies have demonstrated the effectiveness of treating bullying through bibliotherapy, that can become an innovative approach to promote a respectful school environment.…”
Section: Discussionmentioning
confidence: 99%
“…Narrative-based media may be particularly distracting and thus lead to greater energy intake than non-narrative media. Health promotion efforts currently use narrative to model healthy behaviors [34] and to persuade individuals to change their behaviors [35,36]. Narrative may be useful for increasing “self” presence or character identification, which can promote feelings of social support and belonging [37].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies report that the strategy focused at the age-appropriate curriculum intervention and the role of school is important19,28). One of the interesting recent study reported that misperceptions of peer sugar-sweetened beverage consumption norms are pervasive and associated with unhealthy sugar-sweetened beverage consumption behaviors; this result partially explains the complexity of adolescents' psychosocial influences and their own particular teen culture19,29).…”
Section: Recent Advances In Adolescent Nutritionmentioning
confidence: 99%